ANALISIS PENGARUH TINGKAT PARTISIPASI ANGKATAN KERJA, TINGKAT PENDIDIKAN, DAN UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA BARAT - Nisa, Chaerul; Wijaya, Riko Setya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of labor force participation rate, education level, and minimum wage on economic growth in West Java Province. Economic growth is an important indicator in assessing the success of regional development, because it reflects an increase in production capacity and community welfare. The labor force participation rate shows the large working-age population that is active in economic activities, the level of education reflects the quality of human resources, while the minimum wage is a government policy that plays a role in increasing people's purchasing power and labor productivity. This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS) of West Java Province during a certain research period. The analysis method used is multiple linear regression by first conducting a classical assumption test to determine the feasibility of the research model. The results of the study show that the labor force participation rate, education level, and minimum wage simultaneously have a significant effect on economic growth in West Java Province. Partially, education levels and minimum wages have a significant influence on economic growth, while labor force participation rates show a relatively smaller influence.